Whole-body wear-resistant special granite ceramic tile for public places and preparation method thereof
Through polycrystal wear -resistant blank formula and high temperature firing technology, combined with the whole body fabric and digital jet process, the problem of insufficient abrasion resistance of ceramic tiles and the matching of high -hardness wear -resistant decorative layers and precision patterns. Granite ceramic tiles suitable for public places.
Patent Information
- Application Number
- CN202411486780.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The wear resistance of the glaze finish during use during the existing imitation granite ceramic tiles is insufficient, resulting in the surface pattern texture being easily lost and cannot meet the high wear resistance needs of public places.
The polycrystal wear -resistant blank formula is used for high -temperature firing to generate high -hard wear -resistant decorative layers, and through the use of the body fabric and digital jet process to achieve the precise matching and decorative effect of the product pattern texture.
It improves the wear resistance, strength, and pollution resistance of the product, so that it can perfectly present the texture effect of granite stone, and it is suitable for the common wear -resistant special granite ceramic tiles in public places.
Smart Images

Figure CN119371180A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of granite ceramic tiles, and in particular relates to a full-body wear-resistant special granite ceramic tile used in public places and a preparation method thereof. Background Art
[0002] Granite is an igneous rock, generally formed by volcanic materials. It is a hard stone with a hard and dense texture, and can be called the "king of rocks". Granite is extremely hard, resistant to weathering and corrosion, and is the main building material for outdoor public places. However, granite is a non-renewable resource, so people are eager to find a building material that can replace granite. At this time, granite tiles came into being. Granite tiles are beautiful, practical and efficient. They can be widely used in high-end building decoration projects such as villas, gardens, and communities, as well as public scenes with large traffic such as leisure squares, municipal projects, landscaping, subways and railway stations. At the same time, they will not undergo qualitative changes or weathering during use, so they have attracted the attention of consumers.
[0003] Chinese patent CN113716937A discloses a granite-like tile using daily ceramic waste as raw material and a preparation method thereof. This invention patent not only provides a method for preparing granite-like tiles using daily ceramic waste as raw material, but also improves the utilization rate of waste ceramics and reduces the use of colorants and other mineral raw materials through formula design. The process is simple and the production cost is low, which is conducive to the efficient, green, economical and environmentally friendly recycling of daily ceramic waste. Although this method can realize the preparation of granite-like tiles by using daily ceramic waste, the production process is relatively simple, that is, it is achieved by stirring and mixing the mixture and water. The product pattern effect is monotonous and simple, and it cannot fully present the rich texture effect of granite stone. It is difficult to meet the requirements of architectural design, so it is difficult to be widely used.
[0004] Chinese patent CN117247271A discloses a ceramic tile with imitation granite texture and a preparation process thereof. The imitation granite texture of the invention is obtained by using matte frit, perlite, quartz, kaolin, zirconium oxide, magnesium oxide, iron oxide, manganese oxide, titanium oxide and other raw materials in the matte glaze, in combination with a special firing process, so that the fired ceramic tile surface has an off-white base color, and there are dotted or block-shaped black spots distributed on the base color, thereby forming a granite texture and color; although the patent provides a ceramic tile with imitation granite texture and a preparation process thereof, the disadvantage is that the pattern effect of the product produced by the process is relatively monotonous and simple, and it is impossible to completely restore the rich and colorful texture effect of granite stone, which is greatly restricted in practical application.
[0005] In summary, the imitation granite products prepared by fabric or granulation mixing generally have the problem of single texture pattern, and cannot completely imitate the texture effect of granite stone. So far, the glazed ceramic products produced by decorative printing technology such as inkjet or screen printing have the best imitation of granite stone texture. The decorative pattern layer of conventional glazed tiles is generally within 0.1mm, and a layer of transparent glass glaze with a thickness of about 0.2mm needs to be covered on its surface during use. The hardness of the glass glaze layer is relatively poor, and the decorative layer underneath is easily worn during use, resulting in the loss of surface pattern texture. It can be seen that granite glazed ceramic tiles have a fatal flaw when used in public places. The wear resistance of the glaze surface is not enough, and most of them can only be used as ordinary floor tiles. Therefore, the existing production technology of imitation granite ceramic tiles needs to be improved and developed. Summary of the invention
[0006] In view of the deficiencies in the above-mentioned prior art, the technical problem to be solved by the present invention is to provide a kind of special granite ceramic tile which is wear-resistant and can be used in public places and is sintered at high temperature using a polycrystalline phase body formula to generate a high-hardness wear-resistant decorative layer by reaction, so that the product has the high hardness and good wear resistance of natural granite, and has better physical and chemical properties such as pollution resistance, strength and radioactivity, and can perfectly present the texture effect of granite stone. It is a full-body wear-resistant special granite ceramic tile and its preparation method.
[0007] The technical solution of the present invention is the wear-resistant special granite ceramic tile for public places, which is special in that it includes a polycrystalline wear-resistant body layer and a decorative wear-resistant layer. The polycrystalline wear-resistant body is composed of the following raw material components by weight percentage: ball clay 8-15%, high white kaolin 8-15%, mixed mud 10-15%, burnt talc 0-5%, bentonite 3-6%, potassium sodium stone powder 15-25%, finely ground lithium tailings 8-15%, calcined bauxite 4%-8%, fine corundum powder 15-25%, ultrafine zirconium silicate 0-5%, high purity anatase titanium dioxide powder 0-5%, body reinforcing agent 0-1%, and debonding agent 1-3%;
[0008] The multi-crystalline wear-resistant blank formula consists of the following chemical components by weight percentage: Al2O3 30-40wt%, SiO2 45-55wt%, K2O 1-3wt%, Fe2O3 0-2wt%, Na2O 1-3wt%, CaO 0-0.5wt%, MgO 0.5-2.5wt%, and ignition loss 0-5wt%.
[0009] Preferably, the chemical composition of the finely ground lithium tailings consists of the following components by weight: Al2O3 15-20wt%, SiO2 65-75wt%, K2O 2-5wt%, Fe2O3 0-4wt%, Na2O 2-5wt%, CaO 0-2wt%, MgO 0-1wt%, Li2O 0.3-1wt%, trace elements ≥ 0.1wt%, and loss on ignition 0-5wt%; the particle size D50 of the finely ground lithium tailings is between 4μm and 8μm, and the trace elements include rubidium, gallium, strontium, cadmium, and nickel.
[0010] Preferably: the fine corundum powder is α-Al2O3 with Al2O3 content greater than 99%, Fe2O3 content less than 0.1%, and particle size D50 less than 3μm; the ultrafine zirconium silicate has ZrO2 content greater than 64%, and particle size D50 less than 1μm; the high-purity anatase titanium dioxide powder is anatase titanium dioxide with TiO2 content greater than 98%, powder whiteness value ≥96%, 105° volatile matter ≤0.5%, 325 mesh sieve residue less than 0.1%, and particle size D50 less than 1μm.
[0011] Another technical solution of the present invention is a method for preparing the wear-resistant special granite ceramic tile for public places, which is special in that it includes the following steps:
[0012] ⑴ Preparation of polycrystalline wear-resistant green body formula slurry: ball mill the ingredients according to the formula to obtain polycrystalline wear-resistant green body formula slurry, and after iron removal, send it to the transfer slurry pool for storage and aging for later use;
[0013] (2) Preparation of powders of different colors: according to the requirements of the texture pattern design, different ceramic pigments or emulsifiers of set proportions are added to the polycrystalline wear-resistant green body formula slurry in step (1), stirred evenly and sent to a spray drying tower for powdering to obtain colored powders and stored for aging for later use;
[0014] ⑶ Preparation of granular materials of different colors: granulating a part of the color powder of step ⑵ through a granulating device to obtain granular materials of different colors;
[0015] (4) Preparation of mixed powder: the color granular material of step (3) and the color powder of step (2) are mixed evenly according to the designed ratio to obtain a mixed powder for standby use;
[0016] (5) Whole-body fabric: The mixed powder in step (4) is arranged in texture according to the design parameters through the whole-body fabric forming system to obtain a blank layer with a granite texture;
[0017] (6) Pressing and molding: feeding the blank layer of step (5) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank layer;
[0018] ⑺ Drying of the wear-resistant body layer: sending the formed wear-resistant body layer into a roller kiln for drying. The strength of the dried porcelain body is controlled to be 1.5-2.5Mpa;
[0019] (8) Spraying water on the surface of the wear-resistant blank in step (7) to wet it;
[0020] ⑼ Based on the polycrystalline wear-resistant body formula of step ⑴, ceramic colorant, kaolin pigment and raw materials are introduced, and color slurry is obtained through calcination, grinding and spray drying processes;
[0021] ⑽Use the color slurry of step ⑼ to decorate the wetted blank by digital spraying process according to the design pattern to form a decorative wear-resistant layer;
[0022] ⑾ Drying the decorative wear-resistant layer: drying the decorative wear-resistant layer of step ⑽ at a drying temperature of 100 to 200° C. for a drying time of 3 to 8 minutes;
[0023] ⑿ Kiln firing: The ceramic body of step ⑾ is sent into a roller kiln for firing;
[0024] ⒀ The semi-finished products after firing are polished or not polished and ground, and finally wear-resistant special granite ceramic tiles with polished, natural or special-shaped surfaces are obtained.
[0025] As a preferred embodiment: in step (1), the processing of the polycrystalline wear-resistant blank formulation adopts a wet ball milling process, and the median diameter D50 of the slurry is controlled to be 8.5-10.5 μm;
[0026] Preferably, the color powder described in step (2) is composed of the following components by weight percentage: polycrystalline wear-resistant green body formula slurry: 90-100wt%, ceramic colorant: 0-5wt%, emulsifier: 0-10wt%; the color powder is provided with 2-10 different types of colors.
[0027] Preferably, the ceramic colorant in step (2) is composed of the following components by weight: cobalt blue: 0-100wt%, manganese red 0-100wt%, apple green 0-100wt%, chrome green 0-100wt%, orange yellow 0-100wt%, praseodymium yellow 0-100wt%, and cobalt black 0-100wt%.
[0028] Preferably, the opacifier is composed of the following components by weight: zirconium dioxide: 0-100wt%, zirconium silicate: 0-100wt%, titanium dioxide: 0-100wt%.
[0029] As a preferred embodiment, the spray drying tower described in step (2) adopts a pressure spray drying system, uses a nozzle sheet combination with an aperture of 1.5mm to 2.0mm, an atomization pressure of 1.8MPa to 2.6MPa, a drying chamber diameter greater than 10m, a drying output of 10 to 30t / h, and obtains a particle gradation of the powder: the proportion of particles on the 20-mesh sieve is less than 6%, the proportion of particles between 20 and 40 meshes is 20 to 25%, the proportion of particles between 40 and 60 meshes is 40 to 45%, the proportion of particles between 60 and 80 meshes is 15 to 20%, and the proportion of particles below 80 meshes is less than 3%, and the specific gravity of the powder is 0.85 to 0.95g / cm 3 , moisture content is controlled at: 6~8%, and the angle of repose is controlled at 33°~38°.
[0030] As a preferred embodiment: the granulation equipment described in step (3) comprises a discharging device, a scraping device, a pressure roller, a cutter, and a conveyor belt, which is composed of a plurality of discharging devices arranged above the conveyor belt, and a scraping device, a pressure roller, and a cutter respectively arranged behind the discharging device along the running direction of the conveyor belt; the discharging device spreads the color powder of step (2) on the surface of the conveyor belt in multiple layers according to the design parameters, and is scraped and flattened by the scraping device at a fixed height according to the particle thickness requirement, and then pressed into a block by a pressure roller, and finally transported to the cutter to be processed into color granular materials of different colors, sizes, and shapes for storage and standby; the color granular materials are provided with 1 to 5 kinds, the particle size is controlled to be 3 to 20 mm, the thickness is controlled to be 1 to 10 mm, the flexural strength is controlled to be ≥0.1 Mpa, and the density is controlled to be ≥1.0 g / cm 3 ;
[0031] Preferably, the mixed powder in step (4) is provided with 2 to 6 kinds, and is composed of the following components by weight percentage: color powder: 0 to 100 wt%, color particle material: 0 to 100 wt%;
[0032] As a preferred embodiment: the whole body fabric forming system described in step (5) comprises a whole body fabric platform, a pressing and forming platform, and a conveying mechanism; the whole body fabric platform is composed of a fabric mechanism, a transition belt arranged at the bottom of the fabric mechanism, a transition hopper arranged at a position where the transition belt travels at a terminal lower than the transition belt, a grid connected to the bottom of the transition hopper, a movable feeding hopper arranged longitudinally above the conveying mechanism on the side of the pressing and forming platform, and a transfer feeding hopper; the fabric mechanism is designed in multiple groups and arranged above the whole body fabric platform;
[0033] The material distribution mechanism forms a blank layer after the material distribution is completed according to the designed texture pattern. The blank layer is transferred to the transition hopper by the transition belt, and is fixed by the grid and then sent to the mold cavity in the pressing and forming platform arranged at the tail end of the whole material distribution platform through the conveying mechanism. The material is fed by the movable feeding hopper and scraped flat, and then pressed and formed to obtain a wear-resistant blank layer.
[0034] The blank layer is formed by a whole-body cloth forming system to form a granite pattern texture that is consistent from bottom to top, and its thickness can be controlled to be 18mm to 80mm; the pressing pressure in step (6) is greater than 40MPa, and the thickness of the wear-resistant blank layer is controlled to be 9mm to 40mm; the drying time in step (7) is 50 to 120 minutes; the residual moisture of the green blank after drying is ≤0.5%.
[0035] As a preferred embodiment, the color slurry described in step (9) is composed of the following components by weight percentage: 95-100% base slurry, 0-5% ceramic colorant, which are prepared by weight percentage and ground into slurry using a wet ball milling process; the specific gravity of the color slurry is controlled to be 1.75±0.5g / cm 3 , 40° viscosity is 60-150mpa.s, D50 particle size is controlled to be 10-15μm; the ceramic colorant is composed of the following components by weight percentage: cobalt blue 0-100wt%, vanadium zirconium blue 0-100wt%, brown 0-100wt%, package red 0-100wt%, orange 0-100wt%, package yellow 0-100wt%, black 0-100wt%, green 0-100wt%;
[0036] The basic slurry is composed of the following components by weight percentage: 78-90% of light-burned wear-resistant material, 8-20% of kaolin, 0.2-1% of CMC, 0.5-1% of trimer and 0.2-1% of defoamer.
[0037] Preferably, the formula composition of the light-fired wear-resistant material is the same as that of the polycrystalline wear-resistant blank, and the difference is the processing method; the light-fired processing method comprises the following steps:
[0038] ⑴ After the formula is prepared according to the weight percentage, it is ball-milled into slurry according to the wet process;
[0039] (2) The water content of the mud is 35-40%, the viscosity at 40° is 40-80mpa.s, and the D50 particle size is 3-6μm;
[0040] ⑶ Spray-dry the ball-milled slurry to obtain powder, and put the obtained powder into a sagger made of refractory material, or spread it on a flat plate made of refractory material;
[0041] (4) Firing at a temperature of 1050-1150°C to obtain lightly fired wear-resistant material.
[0042] As a preferred embodiment: the digital spraying process described in step ⑽, which uses digital information to directly control the printing process, can realize the printing of 4 to 10 different color slurries at the same time, and the printing amount per square meter is controlled to be 0 to 1800g;
[0043] As a preferred embodiment: the decorative wear-resistant layer described in step ⑽ is formed by CNC spraying process, and a plurality of different color slurries are used for decorative printing according to the design pattern texture. The digital spraying pattern is similar to the pattern texture of the wear-resistant blank layer, and the pattern is narrowed by 0.2-0.4mm, and the thickness of the decorative wear-resistant layer is 0-1mm;
[0044] Preferably, in the kiln firing described in step ⑿, the length of the kiln used is more than 300m, the inner width is greater than 2m, the firing temperature is 1180-1250°C, the firing time is 60-120 minutes, the water absorption of the product after firing is ≤0.5%, and the Ra value of the product out of the kiln refers to the arithmetic mean deviation of the profile, that is, the surface roughness is between 1.5 and 3μm.
[0045] As a preferred embodiment, the processing of step (9) includes two situations:
[0046] ⑴ Directly grind the edge of the product after firing in step ⑿;
[0047] ⑵ The product obtained in step ⑿ is first polished and then edged; the polishing is polishing of the wear-resistant surface; polishing process parameters: polishing machine pressure below 0.6Mpa, polishing speed 15-30m / min, polishing abrasive block combination: 10-15 groups of 3000 mesh elastic abrasive blocks, 15-20 groups of 5000 mesh elastic abrasive blocks, 15-25 groups of 6000 mesh elastic abrasive blocks, 5-10 groups of 2000 mesh fiber abrasive blocks, 5-10 groups of 3000 mesh fiber abrasive blocks, polishing cutting amount is less than 0.05mm, and the Ra value of the product after polishing is ≦0.1μm.
[0048] Compared with the prior art, the present invention has the following beneficial effects:
[0049] ⑴ In the formula of the polycrystalline wear-resistant green body of the present invention, by introducing fine corundum powder, lithium tailings, ultrafine zirconium silicate and titanium dioxide powder, and cooperating with the use of other raw materials, the green body reacts more fully during the sintering process, promoting the formation of a variety of high-hardness wear-resistant crystals including mullite, corundum, zircon, baddeleyite, quartz, cristobalite, rutile, anorthite, cordierite, etc., thereby improving the strength and wear resistance of the ceramic.
[0050] ⑵The present invention provides a whole-body fabric production process and technology. By combining particle preparation, powder mixing, whole-body fabric, digital spraying and other technical processes, the preparation of whole-body wear-resistant special ceramic tiles is completed, the richness of pattern design is expanded, and the product pattern texture is achieved. The texture from the inside to the outside of the layered texture is accurately matched to the whole-body decorative effect.
[0051] ⑶ The present invention provides a method for preparing a digital spraying decorative wear-resistant layer, which promotes the growth of wear-resistant crystals by pre-processing the formulated materials by light firing, so that the product reaches or even exceeds the surface hardness and wear resistance of natural granite.
[0052] (4) The formula of the present invention introduces a large amount of fine corundum powder, which can increase the aluminum content of the formula and at the same time enhance the reaction activity of the green body during the sintering process, thereby promoting the formation of wear-resistant crystals such as mullite, feldspar, and corundum.
[0053] ⑸ The formula of the present invention grinds the lithium tailings into fine powder. In addition to conventional elements such as silicon, aluminum, potassium, and sodium, the lithium tailings also contain special elements such as rubidium, gallium, strontium, cadmium, and nickel, and have a high SiO2 content. Fine grinding can promote the fluxing effect of trace elements, while enhancing the reaction activity of SiO2 and promoting the growth of quartz crystal phases. The introduction of lithium and the formation of quartz crystals can improve the wear resistance of granite ceramic tiles.
[0054] (6) The formula of the present invention introduces ultrafine zirconium silicate and titanium dioxide powder, which can promote the formation of zircon and rutile crystals. Zircon and rutile crystals are both high-hardness materials and can better improve the wear resistance of the product.
[0055] ⑺ The green body formula of the present invention promotes the formation of polycrystalline phases such as mullite, corundum, zircon, baddeleyite, quartz, cristobalite, rutile, anorthite and cordierite by finely grinding lithium tailings, introducing fine corundum powder, ultrafine zirconium silicate and titanium dioxide powder, and cooperating with the use of other raw materials, thereby forming a wear-resistant green body formula with polycrystalline phase components. BRIEF DESCRIPTION OF THE DRAWINGS
[0056] Figure 1 is a diagram showing the physical phase detection results of a ceramic tile prepared by the method of Example 1 of the present invention;
[0057] Figure 2 This is a graph showing the phase detection results of the ceramic tile prepared by the method of Comparative Example 1;
[0058] Figure 3 This is a graph showing the phase detection results of the ceramic tile prepared by the method of Comparative Example 2;
[0059] Figure 4 This is the effect diagram of the wear-resistant special granite ceramic of the present invention;
[0060] Figure 5 It is a schematic diagram of the whole body cloth forming system of the present invention.
[0061] Main component symbols:
[0062] Whole body fabric platform 1 Fabric mechanism 11 Transition belt 12 Transition hopper 13 Grille 14 Transfer hopper 15 Movable feeding hopper 16 Pressing molding platform 2 Cavity 21 Conveying mechanism 3 DETAILED DESCRIPTION
[0063] The present invention will be further described in detail below in conjunction with embodiments:
[0064] Embodiment 1:
[0065] The method for preparing the wear-resistant special granite ceramic tile for public places comprises the following steps:
[0066] ⑴ Preparation of polycrystalline wear-resistant green body formula slurry: ball mill the ingredients according to the formula to obtain polycrystalline wear-resistant green body formula slurry, and after iron removal, send it to the transfer slurry pool for storage and aging for later use;
[0067] The polycrystalline wear-resistant blank formula is composed of the following raw material components by weight percentage: ball clay 9.55%, high white kaolin 10%, mixed mud 12%, burnt talc 4%, bentonite 4%, potassium sodium stone powder 19%, finely ground lithium tailings 10%, calcined bauxite 5%, fine corundum powder 20%, ultrafine zirconium silicate 3%, high purity anatase titanium dioxide powder 2%, blank reinforcing agent 0.35%, debonding agent 1.1%;
[0068] The multi-crystalline wear-resistant blank formulation consists of the following chemical components by weight percentage: Al2O3 37.52wt%, SiO2 49.27wt%, K2O 1.54wt%, Fe2O3 0.66wt%, Na2O 1.65wt%, CaO 0.21wt%, MgO 1.10wt%, TiO2 1.98wt%, ZrO2 1.93wt%, and ignition loss 4.14wt%;
[0069] The processing of the polycrystalline wear-resistant blank formulation adopts a wet ball milling process, and the median diameter D50 of the slurry is 9.7 μm;
[0070] The fine corundum powder formula consists of the following chemical components by weight percentage: Al2O399.94% α-Al2O3, Fe2O3 content of 0.06%, and particle size D50 of 1.86 μm.
[0071] The chemical composition of the finely ground lithium tailings consists of the following components by weight percentage: Al2O3 17.83wt%, SiO2 69.11wt%, K2O 3.50wt%, Fe2O3 0.87wt%, Na2O 3.45wt%, CaO 0.84wt%, MgO 0.42wt%, Li2O 0.41wt%, trace elements 0.18wt%, and ignition loss 3.39wt%; the particle size D50 of the finely ground lithium tailings is 5.4μm, and the trace elements include special elements such as rubidium, gallium, strontium, cadmium, and nickel;
[0072] The ultrafine zirconium silicate has a ZrO2 content of 64.8% and a particle size D50 of 0.82 μm;
[0073] The high-purity anatase titanium dioxide powder is TiO2, with an anatase titanium dioxide content of 98.6%, a powder whiteness value of 97.2%, a volatile matter at 105° of 0.3%, a 325-mesh sieve residue of 0.01%, and a particle size D50 of 0.93 μm;
[0074] ⑵ Preparation of powders of different colors: according to the requirements of texture pattern design, different ceramic pigments or emulsifiers of set proportions are added to the polycrystalline wear-resistant green body formula slurry in step ⑴, stirred evenly and sent to a spray drying tower for powdering to obtain colored powders and store them for aging for later use;
[0075] The color powder is set to eight kinds, and the specific settings are as follows:
[0076] The white powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 90wt%, emulsifier: 10wt%;
[0077] The apricot color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 99.4wt%, manganese red material: 0.3wt%, orange material: 0.3wt%;
[0078] The gray powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 99.7wt%, cobalt black material: 0.2wt%, orange material: 0.1wt%;
[0079] The green color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 99.4wt%, apple green material: 0.5wt%, chrome green material: 0.1wt%;
[0080] The black color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 98.8wt%, cobalt black material: 1.1wt%, manganese red material: 0.1wt%;
[0081] The brown powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 97.3wt%, cobalt black material: 0.4wt%, praseodymium yellow material: 0.7wt%, manganese red material 1.6;
[0082] The yellow powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 98.4wt%, orange material: 0.6wt%, praseodymium yellow material: 1.0wt%;
[0083] The red color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 98.4wt%, manganese red material: 1.3wt%, praseodymium yellow material: 0.3wt%;
[0084] The spray drying tower adopts a pressure spray drying system, uses a nozzle sheet with an aperture of 1.8 mm, an atomization pressure of 2.2 MPa, a drying chamber diameter of 12.5 m, a drying output of 20 t / h, and obtains a particle gradation of the powder: particles on the 20-mesh sieve account for 2.5%, particles between 20 and 40 meshes account for 23.4%, particles between 40 and 60 meshes account for 41.9%, particles between 60 and 80 meshes account for 17.2%, particles below 80 meshes account for 0.85%, and the specific gravity of the powder is 0.92 g / cm 3 , the moisture content is controlled at 6.5%, and the angle of repose is controlled at 35°;
[0085] ⑶ Preparation of granular materials of different colors, granulating a part of the color powder of step ⑵ through a granulating device to obtain granular materials of different colors;
[0086] The color particle materials are provided in four types, specifically white particles, black particles, brown particles, and yellow particles;
[0087] The granulation equipment comprises a discharging device, a scraping device, a pressure roller, a cutter and a conveyor belt, and is composed of a plurality of discharging devices arranged above the conveyor belt, and scraping devices, pressure rollers and cutters respectively arranged behind the discharging devices along the running direction of the conveyor belt; the discharging device spreads a total of four different color powders, namely, the white color powder, the black color powder, the brown color powder and the yellow color powder in step (2) on the surface of the conveyor belt in multiple layers according to design parameters, and the height is determined by the scraping device according to the particle thickness requirement, and after scraping, the pressure roller is pressed into a block, and finally transported to the cutter to be processed into color particle materials of different colors, sizes and shapes for storage and standby; the granulation equipment can prepare particles with various effects, colors, thicknesses and specifications;
[0088] The color particles have a size of 3 to 10 mm, a thickness of 5 mm, a flexural strength of 0.12 Mpa, and a density of 1.61 g / cm 3 :
[0089] (4) Preparation of mixed powder: the color granular material in step (3) and the color powder in step (2) are uniformly mixed according to the designed ratio to obtain a mixed powder for standby use;
[0090] The mixed powder is provided in four types according to the design requirements, including:
[0091] A mixed powder is composed of the following components by weight percentage: white particles: 10wt%, black particles: 5wt%, apricot color powder: 30wt%, gray color powder: 55wt%;
[0092] Mixed powder B is composed of the following components by weight percentage: brown particles: 8wt%, yellow particles: 15wt%, white particles: 5wt%, black color powder: 3wt%, gray color powder: 69wt%;
[0093] Mixed powder C is composed of the following components by weight percentage: brown particles: 5wt%, yellow particles: 20wt%, white particles: 10wt%, red color powder: 15wt%, gray color powder: 40wt%, green color powder: 10wt%;
[0094] The mixed powder D is composed of the following components by weight percentage: yellow powder: 15wt%, apricot powder: 35wt%, black powder: 3wt%, grey powder: 47wt%;
[0095] (5) Whole-body fabrication: the mixed powder in step (4) is arranged in texture according to design parameters by a whole-body fabrication molding system to obtain a blank layer with a granite texture;
[0096] The whole body fabric forming system comprises a whole body fabric platform 1, a pressing and forming platform 2, and a conveying mechanism 3; the whole body fabric platform comprises a fabric mechanism 11, a transition belt 12 arranged at the bottom of the fabric mechanism 11, a transition hopper 13 arranged at a position where the transition belt 12 travels at a terminal lower than the transition belt 12, a grid 14 connected to the bottom of the transition hopper 13, a movable feeding hopper 16 arranged longitudinally above the conveying mechanism 3 on the side of the pressing and forming platform 2, and a transfer feeding hopper 15; the fabric mechanism 11 is designed in multiple groups and arranged at the top of the whole body fabric platform 1;
[0097] The material distributing mechanism 11 forms a blank layer after distributing the material according to the designed texture pattern. The blank layer is transferred to the transition hopper 13 by the transition belt 12, and is fixed by the grid 14 and then sent to the mold cavity 21 in the pressing and forming platform 2 arranged at the tail end of the whole material distributing platform 1 through the conveying mechanism 3. The material is fed by the movable feeding hopper 16 and then flattened and pressed to obtain a wear-resistant blank layer.
[0098] The blank layer is formed by a whole-body fabric forming system to form a consistent granite pattern texture from bottom to top, and its thickness can be controlled to 80mm;
[0099] (6) Pressing and molding, feeding the blank layer of step (5) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank layer;
[0100] The pressing pressure of the pressing molding is 45MPa, and the wear-resistant green body layer has a thickness of 20mm;
[0101] ⑺ Drying of the wear-resistant body layer: sending the formed wear-resistant body layer into a roller kiln for drying. The strength of the dried porcelain body is controlled to be 2.2Mpa;
[0102] The drying time of the wear-resistant green body layer is 110 minutes; the residual moisture of the green body after drying is 0.42%;
[0103] (8) Spraying water on the surface of the wear-resistant blank in step (7) to wet it;
[0104] ⑼ Based on the formula of the polycrystalline wear-resistant green body in step ⑴, pigments and raw materials such as ceramic colorants and kaolin are introduced, and color slurry is obtained through calcination, grinding, spray drying and other processing techniques;
[0105] The color slurry is ground into slurry using a wet ball milling process, and its specific gravity is 1.75g / cm 3 , 40° viscosity 60mpa.s, D50 particle size controlled to 12μm;
[0106] The color paste is provided in eight types according to the design requirements, specifically including:
[0107] The first color slurry is composed of the following components by weight percentage: base slurry: 99wt%, cobalt blue colorant: 1wt%;
[0108] The second color slurry is composed of the following components by weight percentage: base slurry: 97wt%, vanadium zirconium blue colorant: 3wt%;
[0109] The third color slurry is composed of the following components by weight percentage: base slurry: 98wt%, brown colorant: 2wt%;
[0110] The fourth color slurry is composed of the following components by weight percentage: base slurry: 98wt%, wrapped red material: 2wt%;
[0111] The fifth color slurry is composed of the following components by weight percentage: basic slurry: 97wt%, orange color material: 3wt%;
[0112] The sixth color slurry is composed of the following components by weight percentage: base slurry: 97wt%, wrapped yellow material: 3wt%;
[0113] The seventh color slurry is composed of the following components by weight percentage: base slurry: 99wt%, black colorant: 1wt%;
[0114] The eighth color slurry is composed of the following components by weight percentage: base slurry: 98wt%, green colorant: 2wt%;
[0115] The base slurry is composed of the following components by weight percentage: 89% of light-burned wear-resistant material, 9.72% of kaolin, 0.32% of CMC, 0.56% of trimer, and 0.4% of defoamer;
[0116] The formula composition of the light-fired wear-resistant material is consistent with the formula of the polycrystalline wear-resistant blank, except that light-fired processing is required; the light-fired processing method comprises the following steps:
[0117] (9.1) After the formula is prepared according to the weight percentage, it is ball-milled into a slurry according to the wet process. The slurry has a water content of 36%, a viscosity of 60 mpa.s at 40°, and a D50 particle size of 4 μm;
[0118] (9.2) The milled slurry is spray-dried to obtain a powder, and the obtained powder is placed in a sagger made of refractory material, or spread on a flat plate made of refractory material, and fired at a temperature of 1080°C to obtain a lightly fired wear-resistant material;
[0119] ⑽Use the color slurry of step ⑼ to decorate the wetted blank by digital spraying process according to the designed pattern to form a decorative wear-resistant layer;
[0120] The decorative wear-resistant layer is formed by decorative printing of eight different color slurries according to the designed pattern texture using a CNC spraying process. The digital spraying process is a process of directly controlling the printing using digital information, and the printing amount per square is 1400g; the digital spraying pattern is similar to the pattern texture of the wear-resistant blank layer, the pattern is narrowed by 0.2mm, and the thickness of the decorative wear-resistant layer is 0.8mm;
[0121] ⑾ Drying the decorative wear-resistant layer: drying the decorative wear-resistant layer in step ⑽ at a drying temperature of 150° C. for 8 minutes;
[0122] ⑿ Firing, sending the ceramic body of step ⑾ into a roller kiln for firing;
[0123] The firing process uses a kiln with a length of 380m and an inner width of 2.2m, a firing temperature of 1220°C, a firing time of 75 minutes, a water absorption rate of 0.06% after firing, and a Ra value of 1.72μm for the product out of the kiln;
[0124] ⒀ The fired semi-finished products are processed in the post-processing process to finally obtain the wear-resistant special granite ceramic tiles;
[0125] The post-process processing is specifically to polish the product obtained in step ⑿ first and then grind the edges, and the polishing is polishing of the decorative wear-resistant surface; the polishing process parameters are: polishing machine pressure 0.4Mpa, polishing speed 20m / min, polishing abrasive blocks are matched as follows: 12 groups of 3000 mesh elastic abrasive blocks, 18 groups of 5000 mesh elastic abrasive blocks, 20 groups of 6000 mesh elastic abrasive blocks, 6 groups of 2000 mesh fiber abrasive blocks, 8 groups of 3000 mesh fiber abrasive blocks, polishing cutting amount 0.042mm, and the Ra value of the product after polishing is 0.052μm.
[0126] Comparative Example 1:
[0127] The whole body wear-resistant special granite ceramic tile is used in public places. The body formula is composed of the following components by weight percentage (common body formula): 20% of 35# stone powder, 28% of ultra-white washed mud, 24% of potassium-sodium stone powder, 10% of water-abrasive, 3% of superplastic soil, 5% of talcum particles, 8.25% of common mud paste, 0.45% of body reinforcing agent, and 1.3% of degumming agent.
[0128] The difference between Comparative Example 1 and Example 1 is that the polycrystalline wear-resistant green body formula of Example 1 is replaced by a common green body formula. The preparation method of Comparative Example 1 is the same as that of Example 1.
[0129] Specifically, the methods of Example 1 and Comparative Example 1 were used to prepare granite ceramic tiles, and the obtained ceramic tiles and polished natural granite were tested for wear depth, flexural strength, water absorption, and Mohs hardness of unglazed tiles according to the national standard test method for ceramic tiles or the conventional test method for ceramic tiles. The results are shown in Table 1 below:
[0130] Table 1 Performance test comparison of Example 1, Comparative Example 1 and natural granite (polished surface)
[0131]
[0132] The test results of Example 1, Comparative Example 1 and polished natural granite show that when the polycrystalline wear-resistant body formula of the present invention is replaced with a common body formula, the wear resistance, Mohs hardness and flexural strength of the prepared ceramic tile will be significantly reduced. Figure 1 and Figure 2 The physical phase detection results show that the use of a multi-crystalline wear-resistant green body formula generates more crystal phases than an ordinary green body formula, including mullite, corundum, zircon, baddeleyite, quartz, cristobalite, rutile, anorthite, cordierite and other high-hardness wear-resistant crystals. Not only are there many types of crystal phases, but also the content is high. Therefore, the wear resistance of the granite ceramic prepared in Example 1 is significantly higher than that of Comparative Example 1 and natural granite.
[0133] Comparative Example 2:
[0134] The method for preparing the wear-resistant special granite ceramic tile for public places comprises the following steps:
[0135] ⑴ Preparation of polycrystalline wear-resistant green body formula slurry: ball mill the ingredients according to the formula to obtain the polycrystalline wear-resistant green body formula slurry, and send it to the transfer slurry pool for storage and aging after iron removal;
[0136] The polycrystalline wear-resistant blank formulation in the step (1) is composed of the following raw material components by weight percentage: ball clay 9.55%, high white kaolin 10%, mixed mud 12%, burnt talc 4%, bentonite 4%, potassium sodium stone powder 19%, finely ground lithium tailings 10%, calcined bauxite 5%, fine corundum powder 20%, ultrafine zirconium silicate 3%, high purity anatase titanium dioxide powder 2%, blank reinforcing agent 0.35%, debonding agent 1.1%;
[0137] The polycrystalline wear-resistant blank formula is composed of the following raw material components by weight percentage: ball clay 9.55%, high white kaolin 10%, mixed mud 12%, burnt talc 4%, bentonite 4%, potassium sodium stone powder 19%, finely ground lithium tailings 10%, calcined bauxite 5%, fine corundum powder 20%, ultrafine zirconium silicate 3%, high purity anatase titanium dioxide powder 2%, blank reinforcing agent 0.35%, debonding agent 1.1%;
[0138] The multi-crystalline wear-resistant blank formulation consists of the following chemical components by weight percentage: Al2O3 37.52wt%, SiO2 49.27wt%, K2O 1.54wt%, Fe2O3 0.66wt%, Na2O 1.65wt%, CaO 0.21wt%, MgO 1.10wt%, TiO2 1.98wt%, ZrO2 1.93wt%, and ignition loss 4.14wt%;
[0139] The processing of the polycrystalline wear-resistant blank formulation adopts a wet ball milling process, and the median diameter D50 of the slurry is 9.7 μm;
[0140] The fine corundum powder is α-Al2O3 with an Al2O3 content of 99.94%, a Fe2O3 content of 0.06%, and a particle size D50 of 1.86 μm;
[0141] The chemical composition of the finely ground lithium tailings consists of the following components by weight percentage: Al2O3 17.83wt%, SiO2 69.11wt%, K2O 3.50wt%, Fe2O3 0.87wt%, Na2O 3.45wt%, CaO 0.84wt%, MgO 0.42wt%, Li2O 0.41wt%, trace elements 0.18wt%, and ignition loss 3.39wt%; the particle size D50 of the finely ground lithium tailings is 5.4μm, and the trace elements include special elements such as rubidium, gallium, strontium, cadmium, and nickel;
[0142] The ultrafine zirconium silicate has a ZrO2 content of 64.8% and a particle size D50 of 0.82 μm;
[0143] The high-purity anatase titanium dioxide powder is TiO2, with an anatase titanium dioxide content of 98.6%, a powder whiteness value of 97.2%, a volatile matter of 0.3% at 105°, a 325 mesh sieve residue of 0.01%, and a particle size D50 of 0.93 μm;
[0144] ⑵ Preparation of powders of different colors: according to the requirements of texture pattern design, different ceramic pigments or emulsifiers of a certain proportion are added to the polycrystalline wear-resistant green body formula slurry in step ⑴, and after being stirred evenly, they are sent to a spray drying tower for powdering to obtain colored powders and stored for aging for later use;
[0145] The spray drying tower adopts a pressure spray drying system, which uses a nozzle sheet with an aperture of 1.8 mm, an atomization pressure of 2.2 MPa, a drying chamber diameter of 12.5 m, and a drying output of 20 t / h. The particle gradation of the obtained powder is as follows: particles on the 20-mesh sieve account for 2.5%, particles between 20 and 40 meshes account for 23.4%, particles between 40 and 60 meshes account for 41.9%, particles between 60 and 80 meshes account for 17.2%, and particles below 80 meshes account for 0.85%. The specific gravity of the powder is 0.92 g / cm 3 , the moisture content is controlled at 6.5%, and the angle of repose is controlled at 35°;
[0146] The color powder is provided in eight kinds, specifically including:
[0147] The white powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 90wt%, emulsifier: 10wt%;
[0148] The apricot color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 99.4wt%, manganese red material: 0.3wt%, orange material: 0.3wt%;
[0149] The gray powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 99.7wt%, cobalt black material: 0.2wt%, orange material: 0.1wt%;
[0150] The green color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 99.4wt%, apple green material: 0.5wt%, chrome green material: 0.1wt%;
[0151] The black color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 98.8wt%, cobalt black material: 1.1wt%, manganese red material: 0.1wt%;
[0152] The brown powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 97.3wt%, cobalt black material: 0.4wt%, praseodymium yellow material: 0.7wt%, manganese red material 1.6;
[0153] The yellow powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 98.4wt%, orange material: 0.6wt%, praseodymium yellow material: 1.0wt%;
[0154] The red color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 98.4wt%, manganese red material: 1.3wt%, praseodymium yellow material: 0.3wt%;
[0155] The color particle materials are provided in four types, specifically white particles, black particles, brown particles, and yellow particles;
[0156] The granulation equipment includes a discharging device, a scraping device, a pressure roller, a cutter and a conveyor belt, and is composed of a plurality of discharging devices arranged above the conveyor belt, and scraping devices, pressure rollers and cutters arranged behind the discharging device along the running direction of the conveyor belt; the discharging device spreads a total of four different color powders, namely white powder, black powder, brown powder and yellow powder, on the surface of the conveyor belt in multiple layers according to design parameters, and the scraping device scrapes it at a fixed height according to the particle thickness requirements, and then the pressure roller presses it into blocks, and finally conveys it to the cutter to be processed into color granular materials of different colors, sizes and shapes for storage and standby use. The granulation equipment can prepare particles with various effects, colors, thicknesses and specifications.
[0157] The color particle material has a size of 3 to 10 mm, a thickness of 5 mm, a flexural strength of 0.12 Mpa, and a density of 1.61 g / cm 3 :
[0158] ⑶ Preparation of granular materials of different colors, granulating a part of the color powder of step ⑵ through a granulating device to obtain granular materials of different colors;
[0159] (4) Preparation of mixed powder: the color granular material in step (3) and the color powder in step (2) are uniformly mixed according to the designed ratio to obtain a mixed powder for standby use;
[0160] The mixed powder is provided in four types according to the design requirements, specifically including:
[0161] A mixed powder is composed of the following components by weight percentage: white particles: 10wt%, black particles: 5wt%, apricot color powder: 30wt%, gray color powder: 55wt%;
[0162] Mixed powder B is composed of the following components by weight percentage: brown particles: 8wt%, yellow particles: 15wt%, white particles: 5wt%, black color powder: 3wt%, gray color powder: 69wt%;
[0163] Mixed powder C is composed of the following components by weight percentage: brown particles: 5wt%, yellow particles: 20wt%, white particles: 10wt%, red color powder: 15wt%, gray color powder: 40wt%, green color powder: 10wt%;
[0164] The mixed powder D is composed of the following components by weight percentage: yellow powder: 15wt%, apricot powder: 35wt%, black powder: 3wt%, grey powder: 47wt%;
[0165] (5) Whole-body fabrication: the mixed powder in step (4) is arranged in texture according to design parameters by a whole-body fabrication molding system to obtain a blank layer with a granite texture;
[0166] The whole body fabric forming system comprises a whole body fabric platform 1, a pressing and forming platform 2, and a conveying mechanism 3; the whole body fabric platform comprises a fabric mechanism 11, a transition belt 12 arranged at the bottom of the fabric mechanism 11, a transition hopper 13 arranged at a position where the transition belt 12 travels at a terminal lower than the transition belt 12, a grid 14 connected to the bottom of the transition hopper 13, a movable feeding hopper 16 arranged longitudinally above the conveying mechanism 3 on the side of the pressing and forming platform 2, and a transfer feeding hopper 15; the fabric mechanism 11 is designed in multiple groups and arranged at the top of the whole body fabric platform 1;
[0167] The material distributing mechanism 11 forms a blank layer after distributing the material according to the designed texture pattern. The blank layer is transferred to the transition hopper 13 by the transition belt 12, and is fixed by the grid 14 and then sent to the mold cavity 21 in the pressing and forming platform 2 arranged at the tail end of the whole material distributing platform 1 through the conveying mechanism 3. The material is fed by the movable feeding hopper 16 and then flattened and pressed to obtain a wear-resistant blank layer.
[0168] The blank layer is formed by a whole-body fabric forming system to form a consistent granite pattern texture from bottom to top, and its thickness can be controlled to be 80mm;
[0169] (6) Pressing and molding, feeding the blank layer of step (5) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank layer;
[0170] The pressing pressure of the pressing molding is 45MPa / cm 3 , the wear-resistant green body layer has a thickness of 20 mm;
[0171] ⑺ Drying of the wear-resistant body layer: sending the formed wear-resistant body layer into a roller kiln for drying. The strength of the dried porcelain body is controlled to be 2.2Mpa;
[0172] The wear-resistant green body layer is dried for 110 minutes; the residual moisture of the green body after drying is 0.42%;
[0173] (8) Spraying water on the surface of the wear-resistant blank in step (7) to wet it;
[0174] ⑼ Based on the formula of the polycrystalline wear-resistant green body in step ⑴, pigments and raw materials such as ceramic colorants and kaolin are introduced, and color slurry is obtained through calcination, grinding, spray drying and other processing techniques;
[0175] The color slurry is ground into slurry using a wet ball milling process, and its specific gravity is 1.75g / cm 3 , 40° viscosity 60mpa.s, D50 particle size controlled to 12μm;
[0176] The color paste is provided in eight types according to the design requirements, specifically including:
[0177] The first color slurry is composed of the following components by weight percentage: base slurry: 99wt%, cobalt blue colorant: 1wt%;
[0178] The second color slurry is composed of the following components by weight percentage: base slurry: 97wt%, vanadium zirconium blue colorant: 3wt%;
[0179] The third color slurry is composed of the following components by weight percentage: base slurry: 98wt%, brown colorant: 2wt%;
[0180] The fourth color slurry is composed of the following components by weight percentage: base slurry: 98wt%, wrapped red material: 2wt%;
[0181] The fifth color slurry is composed of the following components by weight percentage: basic slurry: 97wt%, orange color material: 3wt%;
[0182] The sixth color slurry is composed of the following components by weight percentage: base slurry: 97wt%, wrapped yellow material: 3wt%;
[0183] The seventh color slurry is composed of the following components by weight percentage: base slurry: 99wt%, black colorant: 1wt%;
[0184] The eighth color slurry is composed of the following components by weight percentage: base slurry: 98wt%, green colorant: 2wt%;
[0185] The basic slurry is composed of the following components by weight percentage: 9.72% ball clay, 10% high white kaolin, 12% mixed mud, 4% burned talc, 4% bentonite, 19% potassium sodium stone powder, 10% finely ground lithium tailings, 5% calcined bauxite, 20% fine corundum powder, 3% ultrafine zirconium silicate, 2% high-purity anatase titanium dioxide powder, 0.32% CMC, 0.56% trimer, and 0.4% defoamer. After the formula is prepared by weight percentage, it is ball-milled into a basic slurry according to a wet process, and the moisture content is controlled to 36%, the viscosity at 40° is 60mpa.s, and the D50 particle size is 4μm.
[0186] ⑽Use the color slurry of step ⑼ to decorate the wetted blank by digital spraying process according to the designed pattern to form a decorative wear-resistant layer;
[0187] The decorative wear-resistant layer is formed by decorative spraying of eight different color slurries according to the designed pattern texture using a CNC spraying process. The digital spraying pattern is similar to the pattern texture of the wear-resistant blank layer, and the pattern is narrowed by 0.2mm. The thickness of the decorative wear-resistant layer is 0.8mm.
[0188] The digital spraying process is a process that uses digital information to directly control the printing process, and the printing volume per square meter is 1400g;
[0189] ⑾ Drying the decorative wear-resistant layer: drying the decorative wear-resistant layer in step ⑽ at a drying temperature of 150° C. for 8 minutes;
[0190] ⑿ Firing, sending the ceramic body of step ⑾ into a roller kiln for firing;
[0191] The firing process uses a kiln with a length of 380m and an inner width of 2.2m, a firing temperature of 1220°C, a firing time of 75 minutes, a water absorption rate of 0.06% after firing, and a Ra value of 1.72μm for the product out of the kiln;
[0192] ⒀ The fired semi-finished products are post-processed to finally obtain the wear-resistant special granite ceramic tiles.
[0193] The post-process processing is specifically to polish the product obtained in step ⑿ first and then grind the edges, and the polishing is polishing of the decorative wear-resistant surface; polishing process parameters: polishing machine pressure 0.4Mpa, polishing speed 20m / min, polishing abrasive block combination: 12 groups of 3000 mesh elastic abrasive blocks, 18 groups of 5000 mesh elastic abrasive blocks, 20 groups of 6000 mesh elastic abrasive blocks, 6 groups of 2000 mesh fiber abrasive blocks, 8 groups of 3000 mesh fiber abrasive blocks, polishing cutting amount 0.042mm, and the Ra value of the product after polishing is 0.052μm.
[0194] The difference between Comparative Example 2 and Example 1 is that the decorative wear-resistant layer formula material is not subjected to light firing processing and is directly prepared and used according to the blank formula.
[0195] Specifically, the methods of Example 1 and Comparative Example 2 were used to prepare granite ceramic tiles, and the obtained ceramic tiles were tested for wear quality at 12,000 revolutions or flexural strength, water absorption, and Mohs hardness performance according to the national standard GB / T4100-2015 for ceramic tiles. The results are shown in Table 2 below:
[0196] Table 2 Performance comparison of Example 1 and Comparative Example 2
[0197]
[0198] The test results of Example 1 and Comparative Example 2 show that when the decorative wear-resistant layer formula material of the present invention is not subjected to light firing, the wear resistance, Mohs hardness and flexural strength of the prepared ceramic tile will decrease. Figure 1 and Figure 3 The phase detection results show that Figure 1 The types and contents of crystal phases are higher than Figure 3 This is because during the light firing process, various materials in the formula react in a solid phase and generate a portion of wear-resistant crystal phase in advance. At the same time, after calcination, the reaction activity of the formula raw materials is improved, which promotes the formation of crystal phase during the secondary firing, so the wear resistance of the product can be better improved.
[0199] Embodiment 2:
[0200] The method for preparing the wear-resistant special granite ceramic tile for public places comprises the following steps:
[0201] ⑴ Preparation of polycrystalline wear-resistant green body formula slurry: ball mill the ingredients according to the formula to obtain the polycrystalline wear-resistant green body formula slurry, and send it to the transfer slurry pool for storage and aging after iron removal;
[0202] The polycrystalline wear-resistant blank formula is composed of the following raw material components by weight percentage: ball clay 9.55%, high white kaolin 10%, mixed mud 12%, burnt talc 4%, bentonite 4%, potassium sodium stone powder 19%, finely ground lithium tailings 10%, calcined bauxite 5%, fine corundum powder 20%, ultrafine zirconium silicate 3%, high purity anatase titanium dioxide powder 2%, blank reinforcing agent 0.35%, debonding agent 1.1%;
[0203] The multi-crystalline wear-resistant blank formulation consists of the following chemical components by weight percentage: Al2O3 37.52wt%, SiO2 49.27wt%, K2O 1.54wt%, Fe2O3 0.66wt%, Na2O 1.65wt%, CaO 0.21wt%, MgO 1.10wt%, TiO2 1.98wt%, ZrO2 1.93wt%, and ignition loss 4.14wt%;
[0204] The processing of the polycrystalline wear-resistant blank formulation adopts a wet ball milling process, and the median diameter D50 of the slurry is 9.7 μm;
[0205] The fine corundum powder is α-Al2O3 with an Al2O3 content of 99.94%, a Fe2O3 content of 0.06%, and a particle size D50 of 1.86 μm;
[0206] The chemical composition of the finely ground lithium tailings is as follows by weight percentage: Al2O3 17.83wt%, SiO2 69.11wt%, K2O 3.50wt%, Fe2O3 0.87wt%, Na2O 3.45wt%, CaO 0.84wt%, MgO 0.42wt%, Li2O 0.41wt%, trace elements: 0.18wt%, ignition loss 3.39wt%; the particle size D50 of the finely ground lithium tailings is 5.4μm, and the trace elements include special elements such as rubidium, gallium, strontium, cadmium, and nickel;
[0207] The ultrafine zirconium silicate has a ZrO2 content of 64.8% and a particle size D50 of 0.82 μm;
[0208] The high-purity anatase titanium dioxide powder is TiO2, with an anatase titanium dioxide content of 98.6%, a powder whiteness value of 97.2%, a volatile matter of 0.3% at 105°, a 325 mesh sieve residue of 0.01%, and a particle size D50 of 0.93 μm;
[0209] ⑵ Preparation of powders of different colors: according to the requirements of texture pattern design, different ceramic pigments or emulsifiers of set proportions are added to the polycrystalline wear-resistant green body formula slurry in step ⑴, stirred evenly and sent to a spray drying tower for powdering to obtain colored powders and store them for aging for later use;
[0210] The spray drying tower adopts a pressure spray drying system, which uses a nozzle sheet with an aperture of 1.8 mm, an atomization pressure of 2.2 MPa, a drying chamber diameter of 12.5 m, and a drying output of 20 t / h. The particle gradation of the obtained powder is as follows: particles on the 20-mesh sieve account for 2.5%, particles between 20 and 40 meshes account for 23.4%, particles between 40 and 60 meshes account for 41.9%, particles between 60 and 80 meshes account for 17.2%, and particles below 80 meshes account for 0.85%. The specific gravity of the powder is 0.92 g / cm 3 , the moisture content is controlled at 6.5%, and the angle of repose is controlled at 35°;
[0211] The color powder is provided in eight kinds, specifically including:
[0212] The white powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 90wt%, emulsifier: 10wt%;
[0213] The apricot color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 99.4wt%, manganese red material: 0.3wt%, orange material: 0.3wt%;
[0214] The gray powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 99.7wt%, cobalt black material: 0.2wt%, orange material: 0.1wt%;
[0215] The green color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 99.4wt%, apple green material: 0.5wt%, chrome green material: 0.1wt%;
[0216] The black color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 98.8wt%, cobalt black material: 1.1wt%, manganese red material: 0.1wt%;
[0217] The brown powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 97.3wt%, cobalt black material: 0.4wt%, praseodymium yellow material: 0.7wt%, manganese red material 1.6;
[0218] The yellow powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 98.4wt%, orange material: 0.6wt%, praseodymium yellow material: 1.0wt%;
[0219] Specifically, the red color powder is composed of the following components by weight percentage: polycrystalline wear-resistant blank formula slurry: 98.4wt%, manganese red material: 1.3wt%, praseodymium yellow material: 0.3wt%;
[0220] The color particle materials are provided in four types, specifically: white particles, black particles, brown particles, and yellow particles;
[0221] The granulation equipment comprises a discharging device, a scraping device, a pressure roller, a cutter and a conveyor belt, and is composed of a plurality of discharging devices arranged above the conveyor belt, and scraping devices, pressure rollers and cutters respectively arranged behind the discharging devices along the running direction of the conveyor belt; the discharging device spreads a total of four different color powders, namely, the white powder, black powder, brown powder and yellow powder in step (2) on the surface of the conveyor belt in multiple layers according to design parameters, and is scraped and flattened by the scraping device at a fixed height according to the particle thickness requirement, and then pressed into a block by the pressure roller, and finally transported to the cutter to be processed into color granular materials of different colors, sizes and shapes for storage and standby; the granulation equipment can prepare particles with various effects, colors, thicknesses and specifications;
[0222] The color particle material size is 3-10mm, the thickness is 5mm, the flexural strength is 0.12Mpa, and the density is 1.61g / cm 3 :
[0223] ⑶ Preparation of granular materials of different colors, granulating a part of the color powder of step ⑵ through a granulating device to obtain granular materials of different colors;
[0224] (4) Preparation of mixed powder: the color granular material in step (3) and the color powder in step (2) are uniformly mixed according to the designed ratio to obtain a mixed powder for standby use;
[0225] The mixed powder is provided in four types according to the design requirements, specifically including:
[0226] A mixed powder is composed of the following components by weight percentage: white particles: 10wt%, black particles: 5wt%, apricot color powder: 30wt%, gray color powder: 55wt%;
[0227] Mixed powder B consists of the following components by weight percentage: brown particles: 8wt%, yellow particles: 15wt%, white particles: 5wt%, black powder: 3wt%, gray powder: 69wt%;
[0228] Mixed powder C is composed of the following components by weight percentage: brown particles: 5wt%, yellow particles: 20wt%, white particles: 10wt%, red color powder: 15wt%, gray color powder: 40wt%, green color powder: 10wt%;
[0229] D mixed powder is composed of the following components by weight percentage: yellow color powder: 15wt%, apricot color powder: 35wt%, black color powder: 3wt%, gray color powder: 47wt%;
[0230] (5) Whole-body fabrication: the mixed powder in step (4) is arranged in texture according to design parameters by a whole-body fabrication molding system to obtain a blank layer with a granite texture;
[0231] The whole body fabric forming system comprises a whole body fabric platform 1, a pressing and forming platform 2, and a conveying mechanism 3; the whole body fabric platform comprises a fabric mechanism 11, a transition belt 12 arranged at the bottom of the fabric mechanism 11, a transition hopper 13 arranged at a position where the transition belt 12 travels at a terminal lower than the transition belt 12, a grid 14 connected to the bottom of the transition hopper 13, a movable feeding hopper 16 arranged longitudinally above the conveying mechanism 3 on the side of the pressing and forming platform 2, and a transfer feeding hopper 15; the fabric mechanism 11 is designed in multiple groups and arranged at the top of the whole body fabric platform 1;
[0232] The material distributing mechanism 11 forms a blank layer after distributing the material according to the designed texture pattern. The blank layer is transferred to the transition hopper 13 by the transition belt 12, and is fixed by the grid 14 and then sent to the mold cavity 21 in the pressing and forming platform 2 arranged at the tail end of the whole material distributing platform 1 through the conveying mechanism 3. The material is fed by the movable feeding hopper 16 and then flattened and pressed to obtain a wear-resistant blank layer.
[0233] The blank layer is formed by the whole body fabric forming system to form a consistent granite pattern texture from bottom to top, and its thickness can be controlled to 80mm
[0234] (6) Pressing and molding, feeding the blank layer of step (5) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank layer;
[0235] The pressing pressure is 45 MPa / cm 3 , the wear-resistant green body layer has a thickness of 20 mm;
[0236] ⑺ Drying of the wear-resistant body layer: sending the formed wear-resistant body layer into a roller kiln for drying. The strength of the dried porcelain body is controlled to be 2.2Mpa;
[0237] The drying time of the wear-resistant green body layer is 110 minutes; the residual moisture of the green body after drying is 0.42%;
[0238] (8) Spraying water on the surface of the wear-resistant blank in step (7) to wet it;
[0239] ⑼ Based on the formula of the polycrystalline wear-resistant green body in step ⑴, pigments and raw materials such as ceramic colorants and kaolin are introduced, and color slurry is obtained through calcination, grinding, spray drying and other processing techniques;
[0240] The color slurry is ground into slurry using a wet ball milling process, and its specific gravity is: 1.75g / cm 3, 40° viscosity: 60mpa.s, D50 particle size controlled to 12μm;
[0241] The color paste is provided in eight types according to the design requirements, specifically including:
[0242] The first color slurry is composed of the following components by weight percentage: base slurry: 99wt%, cobalt blue colorant: 1wt%;
[0243] The second color slurry is composed of the following components by weight percentage: base slurry: 97wt%, vanadium zirconium blue colorant: 3wt%;
[0244] The third color slurry is composed of the following components by weight percentage: base slurry: 98wt%, brown colorant: 2wt%;
[0245] The fourth color slurry is composed of the following components by weight percentage: base slurry: 98wt%, wrapped red material: 2wt%;
[0246] The fifth color slurry is composed of the following components by weight percentage: basic slurry: 97wt%, orange color material: 3wt%;
[0247] The sixth color slurry is composed of the following components by weight percentage: base slurry: 97wt%, wrapped yellow material: 3wt%;
[0248] The seventh color slurry is composed of the following components by weight percentage: base slurry: 99wt%, black colorant: 1wt%;
[0249] The eighth color slurry is composed of the following components by weight percentage: base slurry: 98wt%, green colorant: 2wt%;
[0250] The base slurry is composed of the following components by weight percentage: 89% of light-burned wear-resistant material, 9.72% of kaolin, 0.32% of CMC, 0.56% of trimer, and 0.4% of defoamer;
[0251] The formula composition of the light-fired wear-resistant material is consistent with the formula of the polycrystalline wear-resistant blank, except that light-fired processing is required; the light-fired processing method comprises the following steps:
[0252] ⑴ After the formula is prepared according to the weight percentage, it is ball-milled into slurry according to the wet process;
[0253] (2) The slurry has a water content of 36%, a viscosity of 60 mpa.s at 40°, and a particle size of 4 μm at D50;
[0254] ⑶ Spray-drying the ball-milled slurry to obtain powder;
[0255] (4) The obtained powder is placed in a sagger made of refractory material, or spread on a flat plate made of refractory material;
[0256] (5) Firing at 1080°C to obtain lightly fired wear-resistant material;
[0257] ⑽Use the color slurry of step ⑼ to decorate the wetted blank by digital spraying process according to the designed pattern to form a decorative wear-resistant layer;
[0258] The decorative wear-resistant layer is formed by decorative spraying of eight different color slurries according to the designed pattern texture using a CNC spraying process. The digital spraying pattern is similar to the pattern texture of the wear-resistant blank layer, and the pattern is narrowed by 0.2mm. The thickness of the decorative wear-resistant layer is 0.8mm.
[0259] The digital spraying process is a process that uses digital information to directly control the printing process, and the printing volume per square meter is 1400g;
[0260] ⑾ Drying the decorative wear-resistant layer: drying the decorative wear-resistant layer in step ⑽ at a drying temperature of 150° C. for 8 minutes;
[0261] ⑿ Firing, sending the ceramic body of step ⑾ into a roller kiln for firing;
[0262] The firing process uses a kiln with a length of 380m, an inner width of 2.2m, a firing temperature of 1220°C, a firing time of 75 minutes, a water absorption rate of 0.06% after firing, and a Ra value of 1.72μm for the product out of the kiln;
[0263] ⒀ The fired semi-finished products are processed in the post-processing process to finally obtain the wear-resistant special granite ceramic tiles;
[0264] The post-processing step is specifically to grind the edge of the product obtained in step ⑿ without polishing.
[0265] Granite ceramic tiles were prepared by the method of Example 2, and the obtained ceramic tiles and natural granite were tested for wear depth, flexural strength, water absorption, and Mohs hardness of unglazed tiles according to the national standard test method for ceramic tiles or the conventional test method for ceramic tiles. The results are shown in Table 3 below:
[0266] Table 3 Comparison of performance test between Example 2 and natural granite
[0267]
[0268] It can be seen from the test results of Example 2 and natural granite that the granite ceramic tile prepared by the method of Example 2 has better wear resistance, Mohs hardness and flexural strength than natural granite. This is because the method of Example 2 is used to prepare granite ceramic tiles to produce more high-hardness wear-resistant crystals, including mullite, corundum, zircon, quartz, rutile, anorthite, etc. Here, the Mohs hardness of mullite and anorthite reaches 6, rutile is 6 to 6.5, zircon is 7.5 to 8, and corundum is 9. These high-hardness wear-resistant crystals are not only of many types, but also of high content, thereby improving the wear resistance of the product.
[0269] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made within the scope of the claims of the present invention should fall within the scope of the claims of the present invention.
Claims
1. A wear-resistant special granite ceramic tile for public places, characterized in that: The invention comprises a polycrystalline wear-resistant blank layer and a decorative wear-resistant layer. The polycrystalline wear-resistant blank is composed of the following raw material components by weight percentage: 8-15% ball clay, 8-15% high white kaolin, 10-15% mixed mud, 0-5% burnt talc, 3-6% bentonite, 15-25% potassium sodium stone powder, 8-15% finely ground lithium tailings, 4%-8% calcined bauxite, 15-25% fine corundum powder, 0-5% ultrafine zirconium silicate, 0-5% high-purity anatase titanium dioxide powder, 0-1% blank reinforcing agent, and 1-3% debonding agent. The polycrystalline wear-resistant blank formulation consists of the following chemical components by weight percentage: Al2O330~40wt%, SiO245~55wt%, K2O 1~3wt%, Fe2O30 ~ 2wt%, Na2O 1~3wt%, CaO 0~0.5wt%, MgO 0.5~2.5wt%, loss on ignition 0 ~ 5wt%.
2. The wear-resistant special granite ceramic tile for public places according to claim 1 is characterized in that: The chemical composition of the finely ground lithium tailings consists of the following components by weight percentage: Al2O3 15-20wt%, SiO2 65-75wt%, K2O 2-5wt%, Fe2O3 0-4wt%, Na2O 2-5wt%, CaO 0-2wt%, MgO 0-1wt%, Li2O 0.3-1wt%, trace elements ≥ 0.1wt%, and ignition loss 0-5wt%; the particle size D50 of the finely ground lithium tailings is between 4μm and 8μm, and the trace elements include rubidium, gallium, strontium, cadmium, and nickel.
3. The wear-resistant special granite ceramic tile for public places according to claim 1 is characterized in that: The fine corundum powder is α-Al2O3 with an Al2O3 content of more than 99%, a Fe2O3 content of less than 0.1%, and a particle size D50 of less than 3μm; the ultrafine zirconium silicate has a ZrO2 content of more than 64%, and a particle size D50 of less than 1μm; the high-purity anatase titanium dioxide powder is anatase titanium dioxide with a TiO2 content of more than 98%, a powder whiteness value of ≥96%, 105° volatile matter ≤0.5%, a 325 mesh sieve residue of less than 0.1%, and a particle size D50 of less than 1μm.
4. A method for preparing the wear-resistant special granite ceramic tile for public places according to claim 1, characterized in that: The following steps are involved: ⑴ Preparation of polycrystalline wear-resistant green body formula slurry: ball mill the ingredients according to the formula to obtain polycrystalline wear-resistant green body formula slurry, and after iron removal, send it to the transfer slurry pool for storage and aging for later use; (2) Preparation of powders of different colors: according to the requirements of the texture pattern design, different ceramic pigments or emulsifiers of set proportions are added to the polycrystalline wear-resistant green body formula slurry in step (1), stirred evenly and sent to a spray drying tower for powdering to obtain colored powders and stored for aging for later use; ⑶ Preparation of granular materials of different colors: granulating a part of the color powder of step ⑵ through a granulating device to obtain granular materials of different colors; (4) Preparation of mixed powder: the color granular material of step (3) and the color powder of step (2) are mixed evenly according to the designed ratio to obtain a mixed powder for standby use; (5) Whole-body fabric: The mixed powder in step (4) is arranged in texture according to the design parameters through the whole-body fabric forming system to obtain a blank layer with a granite texture; (6) Pressing and molding: feeding the blank layer of step (5) into the mold cavity of the molding mechanism for pressing to obtain a wear-resistant blank layer; ⑺ Drying of the wear-resistant body layer: sending the formed wear-resistant body layer into a roller kiln for drying. The strength of the dried porcelain body is controlled to be 1.5-2.5Mpa; (8) Spraying water on the surface of the wear-resistant blank in step (7) to wet it; ⑼ Based on the polycrystalline wear-resistant body formula of step ⑴, ceramic colorant, kaolin pigment and raw materials are introduced, and color slurry is obtained through calcination, grinding and spray drying processes; ⑽Use the color slurry of step ⑼ to decorate the wetted blank by digital spraying process according to the design pattern to form a decorative wear-resistant layer; ⑾ Drying the decorative wear-resistant layer: drying the decorative wear-resistant layer of step ⑽, the drying temperature is 100-200° C., and the drying time is 3-8 min; ⑿ Kiln firing: The ceramic body of step ⑾ is sent into a roller kiln for firing; ⒀ The semi-finished products after firing are polished or not polished and ground, and finally wear-resistant special granite ceramic tiles with polished, natural or special-shaped surfaces are obtained.
5. The method for preparing the wear-resistant special granite ceramic tile for public places according to claim 4, characterized in that: Step (1) The processing of the polycrystalline wear-resistant blank formulation adopts a wet ball milling process, and the median diameter D50 of the slurry is controlled to be 8.5-10.5 μm; The granulation equipment described in step (3) comprises a discharging device, a scraping device, a pressure roller, a cutter, and a conveyor belt, which is composed of a plurality of discharging devices arranged above the conveyor belt, and a scraping device, a pressure roller, and a cutter respectively arranged behind the discharging device along the running direction of the conveyor belt; the discharging device spreads the color powder of step (2) on the surface of the conveyor belt in multiple layers according to the design parameters, and the scraping device is used to scrape it at a fixed height according to the particle thickness requirement, and then it is pressed into a block by a pressure roller, and finally transported to the cutter to be processed into color granular materials of different colors, sizes, and shapes for storage and standby; the color granular materials are provided with 1 to 5 kinds, the particle size is controlled to be 3 to 20 mm, the thickness is controlled to be 1 to 10 mm, the flexural strength is controlled to be ≥0.1 Mpa, and the density is controlled to be ≥1.0 g / cm 3 ; In step (4), the mixed powder is provided with 2 to 6 kinds, and is composed of the following components by weight percentage: color powder: 0 to 100 wt%, color granular material: 0 to 100 wt%; The whole body fabric forming system described in step (5) comprises a whole body fabric platform, a pressing and forming platform, and a conveying mechanism; the whole body fabric platform is composed of a fabric mechanism, a transition belt arranged at the bottom of the fabric mechanism, a transition hopper arranged at a position where the transition belt travels at a terminal lower than the transition belt, a grid connected to the bottom of the transition hopper, a movable feeding hopper arranged longitudinally above the conveying mechanism on the side of the pressing and forming platform, and a transfer feeding hopper; the fabric mechanism is designed in multiple groups and arranged above the whole body fabric platform; The material distribution mechanism forms a blank layer after the material distribution is completed according to the designed texture pattern. The blank layer is transferred to the transition hopper by the transition belt, and is fixed by the grid and then sent to the mold cavity in the pressing and forming platform arranged at the tail end of the whole material distribution platform through the conveying mechanism. The material is fed by the movable feeding hopper and scraped flat, and then pressed and formed to obtain a wear-resistant blank layer. The blank layer is formed by a whole-body fabric forming system to form a consistent granite pattern texture from bottom to top, and its thickness can be controlled to be 18mm to 80mm; In step (6), the pressing pressure is greater than 40 MPa, and the thickness of the wear-resistant green body layer is controlled to be 9 mm to 40 mm; The drying time in step (7) is 50 to 120 minutes; the residual moisture of the green body after drying is ≤0.5%.
6. The method for preparing the wear-resistant special granite ceramic tile for public places according to claim 4, characterized in that: The spray drying tower described in step (2) adopts a pressure spray drying system, uses a nozzle sheet combination with an aperture of 1.5 mm to 2.0 mm, an atomization pressure of 1.8 MPa to 2.6 MPa, a drying chamber diameter greater than 10 m, a drying output of 10 to 30 t / h, and obtains a particle gradation of the powder: the proportion of particles on the 20-mesh sieve is <6%, the proportion of particles between 20 mesh and 40 mesh is 20 to 25%, the proportion of particles between 40 mesh and 60 mesh is 40 to 45%, the proportion of particles between 60 mesh and 80 mesh is 15 to 20%, and the proportion of particles below 80 mesh is <3%, and the specific gravity of the powder is 0.85 to 0.95 g / cm 3 , the moisture content is controlled at: 6-8%, and the angle of repose is controlled at 33°-38°; The color powder in step (2) is composed of the following components by weight percentage: polycrystalline wear-resistant body formula slurry: 90-100wt%, ceramic colorant: 0-5wt%, emulsifier: 0-10wt%; The color powder is provided with 2 to 10 different types of colors; The ceramic pigment in step (2) is composed of the following components by weight percentage: 0-100wt% cobalt blue, 0-100wt% manganese red, 0-100wt% apple green, 0-100wt% chrome green, 0-100wt% orange yellow, 0-100wt% praseodymium yellow, and 0-100wt% cobalt black; The opacifying agent is composed of the following components by weight percentage: zirconium dioxide: 0-100wt%, zirconium silicate: 0-100wt%, titanium dioxide: 0-100wt%.
7. The method for preparing the wear-resistant special granite ceramic tile for public places according to claim 4, characterized in that: The color slurry described in step (9) is composed of the following components by weight percentage: 95-100% base slurry and 0-5% ceramic colorant, which are prepared by weight percentage and ground into slurry using a wet ball milling process; the specific gravity of the color slurry is controlled to be 1.75±0.5g / cm 3 , 40° viscosity is 60~150mpa.s, D50 particle size is controlled to be 10~15μm; The ceramic pigment is composed of the following components by weight percentage: cobalt blue: 0-100wt%, vanadium zirconium blue: 0-100wt%, brown: 0-100wt%, package red: 0-100wt%, orange: 0-100wt%, package yellow: 0-100wt%, black: 0-100wt%, green: 0-100wt%; The basic slurry is composed of the following components by weight percentage: 78-90% of light-burned wear-resistant material, 8-20% of kaolin, 0.2-1% of CMC, 0.5-1% of trimer and 0.2-1% of defoamer.
8. The method for preparing the wear-resistant special granite ceramic tile for public places according to claim 7, characterized in that: The formula composition of the lightly fired wear-resistant material is the same as that of the polycrystalline wear-resistant blank, except for the processing method; the lightly fired processing method comprises the following steps: ⑴ After the formula is prepared according to the weight percentage, it is ball-milled into slurry according to the wet process; (2) The water content of the mud is 35-40%, the viscosity at 40° is 40-80mpa.s, and the D50 particle size is 3-6μm; ⑶ Spray-dry the ball-milled slurry to obtain powder, and put the obtained powder into a sagger made of refractory material, or spread it on a flat plate made of refractory material; (4) Firing at a temperature of 1050-1150°C to obtain lightly fired wear-resistant material.
9. The method for preparing the wear-resistant special granite ceramic tile for public places according to claim 4, characterized in that: The digital spraying process described in step ⑽ uses digital information to directly control the printing process, and can simultaneously realize the printing of 4 to 10 different color slurries, and the printing amount per square is controlled to be 0 to 1800g; the decorative wear-resistant layer described in step ⑽ adopts a CNC spraying process, and a plurality of different color slurries are used for decorative printing according to the design pattern texture. The digital spraying pattern is similar to the pattern texture of the wear-resistant blank layer, and the pattern is narrowed by 0.2 to 0.4mm, and the thickness of the decorative wear-resistant layer is 0 to 1mm; The kiln firing described in step ⑿ adopts a kiln length of more than 300m, an inner width of more than 2m, a firing temperature of 1180-1250°C, a firing time of 60-120 minutes, a water absorption rate of the product after firing of ≤0.5%, and an Ra value of the product out of the kiln, wherein the Ra value refers to the arithmetic mean deviation of the profile, that is, the surface roughness is between 1.5 and 3μm.
10. The method for preparing the wear-resistant special granite ceramic tile for public places according to claim 4, characterized in that: The processing of step ⒀ includes two situations: ⑴ Directly grind the edge of the product after firing in step ⑿; ⑵ The product obtained in step ⑿ is first polished and then edged; the polishing is polishing of the wear-resistant surface; polishing process parameters: polishing machine pressure below 0.6Mpa, polishing speed 15-30m / min, polishing abrasive block combination: 10-15 groups of 3000 mesh elastic abrasive blocks, 15-20 groups of 5000 mesh elastic abrasive blocks, 15-25 groups of 6000 mesh elastic abrasive blocks, 5-10 groups of 2000 mesh fiber abrasive blocks, 5-10 groups of 3000 mesh fiber abrasive blocks, polishing cutting amount is less than 0.05mm, and the Ra value of the product after polishing is ≦0.1μm.
Citation Information
Patent Citations
Granite-imitated ceramic tile taking domestic waste ceramic as raw material and preparation method thereof
CN113716937A
Granite grain-imitated ceramic tile and preparation process thereof
CN117247271A
Corrosion resistant brick
CN104355606A
Thin ceramic rock plate and preparation method thereof
CN111470856A
Preparation method of deep-color granite ceramic tile and deep-color granite ceramic tile
CN113307604A
Cited By
Digital slurry decorated ceramic tile with decoration durability and preparation method of digital slurry decorated ceramic tile
CN119350066A
Digital paste-decorated ceramic tile with decorative durability and preparation method thereof
CN119350066B